Social psychology / Elliot Aronson; Timothy D Wilson; Robin M Akert - Aronson, Elliot
A scientific approach to social psychology which uses real-world examples to illustrate methods of research and key concepts and theories. This revised edition offers a balance of classical and modern research and pedagogical features encourage active learning. Chapters can be used in any order.